Determinants of innovation in European construction firms - Barata, José M.; Fontainha, Elsa (Technological and Economic Development of Economy, 2017)
The research aims to identify the determinants of process and product innovation in a traditional and low-tech sector, supported in micro, small and medium-sized enterprises (SMEs), specifically European Construction Sector. The study uses micro data from the e-Business Survey of the European Commission. The dependent variables studied are binary (presence or absence of process or/and product innovation). The explanatory variables considered are: suppliers, clients, market orientation, turnover growth and size. In addition, some national context variables – GDP per capita and R&D weight in GDP – are also tested. The results show that the sector of construction innovates, and the factors that contribute more to this innovation are suppliers and growth of business. It is also concluded that firm size is more relevant for process innovation than for product innovation, and companies that are guided by international markets innovate more than those that focus on local and regional markets.First published online: 29 Jan 2017